Procedure for Purchasing Raw Materials on Credit at PT Bernofarm Pharmaceutical Company Sidoarjo - Kamelia, Nila; Sri Trisnaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study uses a qualitative descriptive approach that aims to systematically describe the procedure for purchasing raw materials on credit at PT Bernofarm Pharmaceutical Company. The study focuses on various stages of purchasing, coordination between related departments (such as PPIC, purchasing, QC, warehouse, and accounting), and the use of documents and recording tools such as Microsoft Excel and ERP systems. This study is motivated by the importance of implementing standard purchasing procedures to ensure smooth production processes, accuracy of debt recording, and quality of raw materials. Primary data were obtained through direct observation during internship activities and unstructured interviews with management, especially the accounting department. Meanwhile, secondary data were obtained through a review of relevant literature to strengthen the analysis and discussion. The analysis technique was carried out qualitatively through the process of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the procedure for purchasing raw materials on credit at PT Bernofarm is in line with the principles of internal control based on the COSO framework and meets applicable quality management standards, such as GMP/CPOB and ISO. Each stage from supplier evaluation, quality inspection, to debt repayment shows orderly and documented control. Thus, the procedures implemented support the operational effectiveness and integrity of the company's financial data.